2010
DOI: 10.1093/abbs/gmq084
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and expression pattern of two enolase genes from the Chinese oak silkworm, <italic>Antheraea pernyi</italic>

Abstract: In this study, two enolase genes were isolated and characterized from the Chinese oak silkworm, Antheraea perny, which were designated as enolase I and II, respectively. The enolase I cDNA sequence was 1712 bp with an open reading frame (ORF) of 1302 bp encoding 433 amino acids. The enolase II cDNA sequence was 1549 bp with an ORF of 1296 bp encoding 431 amino acids. The amino acid sequences of the two genes share several conserved features/sites of enolase. Antheraea pernyi enolase I shows 93% -97% sequence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…The phylogenetic trees constructed in this study supported the monophyly of Lepidoptera, Diptera, Coleoptera, and Hymenoptera. These results are consistent with the traditional classiÞcation, and other molecular data, such as enolase gene (Liu et al 2010b), lysophospholipase gene (Liu et al 2010c), and will die slowly gene ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The phylogenetic trees constructed in this study supported the monophyly of Lepidoptera, Diptera, Coleoptera, and Hymenoptera. These results are consistent with the traditional classiÞcation, and other molecular data, such as enolase gene (Liu et al 2010b), lysophospholipase gene (Liu et al 2010c), and will die slowly gene ).…”
Section: Resultssupporting
confidence: 89%
“…In recent years, many housekeeping genes, such as ribosomal protein gene (Hou et al 2008), myosin light chain 2 gene (Yang et al 2008, Liu et al 2010d, enolase gene (Regier et al 2009, Liu et al 2010b, lysophospholipase gene (Liu et al 2010c), and will die slowly gene , have been reported to be a new molecular tool for phylogenetic inference of life organs. Our study showed that the phylogenetic analysis based on the Sps amino acid sequences clearly separated the known bacterial, fungal, invertebrate, and vertebrate Sps proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese oak moth ( Antheraea pernyi ) is a lepidopteran insect, and its enolaseI and enolaseII genes corresponded well with BmEno1 and BmEno2. A. pernyi enolaseII contains the same metal-binding and substrate-binding amino acid residues as BmEno2 and BmEnoC [17]. Our phylogenetic analysis showed that BmEno1 was close to the cluster containing insect enolases, such as those from D. melanogaster , T. castaneum and A. mellifera .…”
Section: Discussionmentioning
confidence: 94%
“…In invertebrates, there are evidences for the presence of more than one enolase gene with differential regulation. For instance, two enolase genes have been reported for the silkworm Antheraea pernyi (Liu et al, 2010) and for Toxoplasma gondii (Dzierszinski et al, 2001). In S. japonicum, southern blot analysis suggested that this parasite also contains more than one enolase gene (Waine et al, 1993).…”
Section: Discussionmentioning
confidence: 99%